Mutation spectrum of hyperphenylalaninemia candidate genes and the genotype-phenotype correlation in the Chinese population - Wang, Ruifang; Blau, Nenad (Clinica chimica acta, 2018)
BACKGROUND: Hyperphenylalaninemia (HPA) is an inherited metabolic disorder that is caused by a deficiency of phenylalanine hydroxylase (PAH) or tetrahydrobiopterin. The prevalence of HPA varies widely around the world. - METHODS: A spectrum of HPA candidate genes in 1020 Chinese HPA patients was reported. Sanger sequencing, next generation sequencing (NGS), multiplex ligation-dependent probe amplification (MLPA) and quantitative real-time PCR (qRT-PCR) were applied to precisely molecular diagnose HPA patients. The allelic phenotype values (APV) and genotypic phenotype values (GPV) were calculated in PAH-deficient patients based on a recently developed formula. - RESULTS: Apart from genetic diagnoses confirmed in 915 HPA patients (89.7%) by Sanger sequencing, pathogenic variants were discovered in another 57 patients (5.6%) through deep detections (NGS, MLPA and qRT-PCR). We identified 196, 42, 10 and 2 variants in PAH, PTS, QDPR and GCH1, respectively. And a total of 47 novel variants were found in these genes. Through the APV and GPV calculations, it was found that the new GPV system was well correlated with metabolic phenotypes in most PAH-deficient patients. - CONCLUSIONS: More HPA candidate variants were identified using new molecular diagnostic methods. The new APV and GPV system is likely to be highly beneficial for predicting clinical phenotypes for PAH-deficient patients.
Gesehen am 19.06.2019